2016
DOI: 10.4329/wjr.v8.i7.656
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal ultrasonography of the pediatric gastrointestinal tract

Abstract: Ultrasound is an invaluable imaging modality in the evaluation of pediatric gastrointestinal pathology; it can provide real-time evaluation of the bowel without the need for sedation or intravenous contrast. Recent improvements in ultrasound technique can be utilized to improve detection of bowel pathology in children: Higher resolution probes, color Doppler, harmonic and panoramic imaging are excellent tools in this setting. Graded compression and cine clips provide dynamic information and oral and intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 99 publications
0
35
0
4
Order By: Relevance
“…Ultrasound examination may be required if physical findings are inconclusive or in cases of acute scrotum [18]. Ultrasound can also be used in assessing peristalsis, wall thickness and vascularity of the bowel in the hernia sac [19]. Chen et al reported that ultrasound is 95.5% accurate in detecting inguinal hernia in boys [20].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound examination may be required if physical findings are inconclusive or in cases of acute scrotum [18]. Ultrasound can also be used in assessing peristalsis, wall thickness and vascularity of the bowel in the hernia sac [19]. Chen et al reported that ultrasound is 95.5% accurate in detecting inguinal hernia in boys [20].…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate peristalsis, some examiners recommend administering antispasmolytics prior to CEUS exams. Pre-contrast US assesses the diseased bowel location, total length, wall thickness, morphology of the bowel wall, and vascularity using color/power Doppler US [ 29 , 30 ]. Other imaging features examined on baseline US include echogenicity and vascularity of the mesenteric fat, presence of enlarged lymph nodes, and complications such as inflammatory mass, abscesses, strictures and fistulae.…”
Section: Imaging Technique For Bowel Contrast-enhanced Ultrasoundmentioning
confidence: 99%
“…6 Under normal condition, five echo layers, namely, superficial mucosa, muscularis mucosa, submucosa, muscularis proper, and serosa, could be demonstrated by ultrasonography. 7 Involvement of the echo layers might help determine local infiltration of GIST in the stomach wall. We recently treated a gastric GIST with intact five layers of stomach wall between the gastric cavity and the tumor, which turned out to be a serosa-derived GIST.…”
Section: Introductionmentioning
confidence: 99%